#socialiseresponsibly. Analyzing the Rhetorical Structure of Heineken TV Commercials During the Pandemic - Wildfeuer, Janina; Coffie, Joseph Adika (Frontiers in Communication, 2022)
This work analyzes the efforts by the company Heineken to address in their marketing campaigns the social responsibility and well-being of their customers during the pandemic. By particularly looking at the audio-visual design strategies used in 15 TV commercials produced and published during the years 2020-2022, a multimodal analysis of the filmic montage structures examines how the company establishes a coherent process of core marketing and convinces recipients to socialize responsibly under pandemic conditions. The analysis follows the current trend in empirical multimodality research to pursue analyses of digital corpora with the theories and methods developed in the field. Particularly, it uses an ELAN annotation scheme for the description of specific camera techniques (such as camera distance and perspective) as well as the discourse relations holding between the shots and segments identified in the commercials. The findings show that the company mainly uses one specific type of rhetorical structure, the narrative commentary, that puts the social actors shown in many different scenes into the foreground and therefore strongly focuses on the company’s strategy of positive social behavior.